Pengakuan Anak Biologis di Luar Nikah - Fadli F; Andi Muh. Taqiyuddin BN (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This study aims to reveal the status of children out of wedlock in a review of Islamic law and positive law. This research is qualitative, and the type of research is library research. The data collection method used is a literature study. The research results show that; 1) The status of children out of wedlock given Islamic law, that is, a child out of wedlock is only assigned to his mother so that the child can only inherit from his mother and his mother's family and vice versa. As for his biological father, he cannot inherit because there is no kinship relationship. Suppose the child born as a result of adultery (out of wedlock) turns out to be a girl, and after adulthood, the child will marry. In that case, the natural (genetic) father has no right or is illegal to marry her (become a marriage guardian), who becomes the guardian his marriage is the guardian of the Judge. 2) The status of children out of wedlock in a positive legal review, namely children out of wedlock, is recognized by the state since the Constitutional Court Decision No. 46/PUU-VIII/2010, which states that a child out of wedlock is still recognized as a legitimate child in civil terms both by his mother and his mother's family and the man who is said to be his father which can be proven based on science and technology.